Human periodontal ligament stem cells suppress T‐cell proliferation via down‐regulation of non‐classical major histocompatibility complex‐like glycoprotein CD1b on dendritic cells. (29th March 2016) - Shin, C.; Kim, M.; Han, J.‐A.; Choi, B.; Hwang, D.; Do, Y.; Yun, J.‐H.
Abstract : Background and Objective: Periodontal ligament stem cells (PDLSCs) from the periodontal ligament tissue were recently identified as mesenchymal stem cells (MSCs). The capabilities of PDLSCs in periodontal tissue or bone regeneration have been reported, but their immunomodulatory role in T‐cell immune responses via dendritic cells (DCs), known as the most potent antigen‐presenting cell, has not been studied. The aim of this study is to understand the immunological function of homogeneous human STRO‐1 + CD146 + PDLSCs in DC‐mediated T‐cell immune responses to modulate the periodontal disease process. Material and Methods: We utilized highly purified (> 95%) human STRO‐1 + CD146 + PDLSCs and human bone marrow mesenchymal stem cells (BMSCs). Each stem cell was co‐cultured with human monocyte‐derived DCs in the presence of lipopolysaccharide isolated from Porphyromonas gingivalis, a major pathogenic bacterium responsible for periodontal disease, in vitro to examine the immunological effect of each stem cell on DCs and DC‐mediated T‐cell proliferation. Results: We discovered that STRO‐1 + CD146 + PDLSCs, as well as BMSCs, significantly decreased the level of non‐classical major histocompatibility complex glycoprotein CD1b on DCs, resulting in defective T‐cell proliferation, whereas most human leukocyte antigens and the co‐stimulatory molecules CD80 and CD86 in/on DCs were not significantly affected by the presence of BMSCs or STRO‐1 + CD146 + PDLSCs. Conclusions: This study unveiled an immunomodulatory role of STRO‐1 + CD146 + PDLSCs in negatively regulating DC‐mediated T‐cell immune responses, demonstrating their potential to be utilized in promising new stem cell therapies.